TP53 rs1042522 polymorphism and early-onset breast cancer - Icen-Taskin, Irmak; Irtegun-Kandemir, Sevgi; Munzuroglu, Omer (Wolters Kluwer Medknow Publications, 2020)
Background: Breast cancer is the leading cause of cancer deaths among women. Early-onset breast cancer is well recognized as it clinically differs from old-age diagnosed breast neoplasms. TP53 rs1042522 polymorphism relates to the risk of breast neoplasms, but this relationship in Turkish early-onset breast cancer patients has not been investigated yet. We aimed to search the relationship between TP53 rs1042522 polymorphism and young Turkish breast cancer patients. Materials and Methods: Ninety-six female breast cancer patients who were <= 40 years of age and 96 healthy controls were enrolled in our study. Participants were genotyped by the hybridization probe system. Results: We identified that the genotype frequencies of rs1042522 were significantly different between controls and cases (P = 0.027). Participants carrying CG genotype had also reduced breast cancer risk (odds ratio = 0.4196, 95% confidence interval: 0.1941-0.9067, P = 0.027). Our results revealed that there is an association between GG and CG + CC genotype groups with progesterone receptor (PgR) status (P = 0.0219). Conclusion: Our findings indicate that the CG genotype is a protective factor against breast neoplasms. No other clinicopathologic parameters except for PgR status were found to be related to rs1042522 polymorphism in young Turkish breast cancer patients.
Keywords: Breast neoplasms; early onset; genotype; rs1042522; TP53